Rancang Bangun Sistem Otomatisasi Irigasi Pipa Lahan Sawah Berbasis Tenaga Surya - Sudirman Sirait; Satyanto K. Saptomo; Muhammad Yanuar J. Purwanto (Balai Teknik Irigasi, 2015)
Design of optimum irrigation equipped by an automatic control system can keep the water level in the soil at a certain level according to the needs of plants, It can increase the productivity and efficiency of irrigation water use in paddy fields. Automatic control system was constructed by utilizing digital technology, microcontroller and sensor networks. Arduino Uno ATMega328P microcontroller was used as an automatic controller to operate electrical valve Valworx 561086 based on soil moisture conditions and water level in paddy fields determined by sensor. Water level of the field was set at a range of 0 to 5 cm setpoint reference to operate electrical valve Valworx 561086. System microcontroller limits the duration of time for setting the opening and closing electrical valve Valworx 561086 for 300 seconds with a rotation of 90that can reduce battery consumption. The system is operated by solar energy, which consists of solar panel, charge controller and battery, and can be operated for 24 hours without operators attending. Irrigation system test was operated by applying intermittent irrigation and water did not flow continuously in paddy field. The result shown that the automatic irrigation system can keep the water level in paddy fields between the desired setpoint range.